Distribution and Toxic Equipvalent Assessement of Polycyclic Aromatic Hydrocarbons (Pahs) in Particulate Matter Emmited from Rice Straw Open Field Burning in Hanoi - Thuy, Pham Chau; Tuyen, Le Huu (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 2DO - 10.25073/2588-1140/vnunst.5192, 2021)
This study investigated the distribution of PAHs content in particulate matter emitted from the open burning of rice straw in Hanoi. Fine particles (PM 2.5 ) was collected using a MiniVol TAS device and the total suspended particles (TSP) was collected using a high-volume sampler Staplex. PAHs in particulate matter were analyzed by HPLC-FL with fluorescent detector. The results showed that 4-ring PAHs was dominant in particles emitted from rice straw burning, especially the most abundant PAHs was Flu: 57.8  37.1 and 64.8  34.9 µg/g in PM 2.5 and TSP, respectively. However, the accumulation of PAHs with a higher rings number, especially the percentage of BaP in total 9PAHs in PM 2.5 emitted from rice straw open burning was 2 times higher than that in the background samples, while the ratio of BaP in total 9PAHs in TSP from burning smoke is smaller than that of background samples. The carcinogenic potential of fine particles emitted from rice straw open burning calculated by BaPeq are 20 times higher than that of the background sample. Although the concentration of atmospheric particles - bound BaP in the present study (1.0  0.8 ng / m 3 ) is lower than that in urban and traffic areas, the average value of BaP is still 8.7 times higher than the value recommended by the WHO. The results of this study show a picture of the toxic levels of atmospheric particles and particles emitted from rice straw open burning, providing clearer evidence to understand the adverse effects of rice straw open burning on atmospheric environment and health effect.